Analysis of Lexical Aspects of Four Song Lyrics in "Selamat Ulang Tahun" Album by Nadin Amizah - Anjelia Ratu Oasis; Anugrah Dinda Juliawan; Neneng Nurjanah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to determine the lexical aspects contained in the four song lyrics in the album "Selamat Ulang Tahun" by Nadin Amizah. This study used descriptive qualitative method. The data sources for this research are four song lyrics in the album "Selamat Ulang Tahun" by Nadin Amizah which consists of the songs “Beranjak Dewasa”, “Sorak Sorai”, “Bertaut”, and “Taruh”. The data in this study are words, phrases, clauses, and sentences from four song lyrics from the album "Selamat Ulang Tahun" by Nadin Amizah. Data collection techniques in this study used documentation and note-taking techniques. The data analysis technique in this study uses the Analysis Interactive model which divides its analysis activities into four parts, namely data collection, data reduction, data presentation, and drawing conclusions or data verification. From the results of this study it was found that there are several lexical aspects in the four song lyrics in the album "Selamat Ulang Tahun" by Nadin Amizah namely repetition, synonymy, antonym, collocation, and hyponymy.